2015
DOI: 10.1088/2053-1583/2/4/045015
|View full text |Cite
|
Sign up to set email alerts
|

Second Harmonic Generation in WSe 2

Abstract: Second harmonic generation of single-and few-layer mechanically exfoliated tungsten diselenide (WSe 2 ) samples are studied. The value of the effective second-order nonlinear susceptibility for monolayer WSe 2 is obtained, being three orders of magnitude larger than the values usually reported for other nonlinear bulk crystals. The presence of a monolayer is certified by symmetry analysis of the Raman modes and the occurrence of a direct band gap. Our results on WSe 2 solidify the family of transition metal di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(59 citation statements)
references
References 30 publications
4
54
1
Order By: Relevance
“…The MoS 2 measurements are in excellent agreement with refs 27 and 28, which provides support for our d s 1T′ MoTe 2 values. It is important to note that the d s values reported in refs 29, 30, and 32 are an order of magnitude larger compared to refs 27 and 28 because different calibration procedures were used. Unlike the resonance for MoS 2 , 1T′ MoTe 2 shows d s increases as the excitation wavelength increases as expected given the electronic states at ≈1 eV at the Γ point.…”
Section: Resultsmentioning
confidence: 90%
“…The MoS 2 measurements are in excellent agreement with refs 27 and 28, which provides support for our d s 1T′ MoTe 2 values. It is important to note that the d s values reported in refs 29, 30, and 32 are an order of magnitude larger compared to refs 27 and 28 because different calibration procedures were used. Unlike the resonance for MoS 2 , 1T′ MoTe 2 shows d s increases as the excitation wavelength increases as expected given the electronic states at ≈1 eV at the Γ point.…”
Section: Resultsmentioning
confidence: 90%
“…34 Since then, both the experiments and calculations indicated that A and B exciton could also enhance SHG. 48,57,59,61,65,66,146,147 Typically, Wang et al recorded an enhancement up to three order of magnitude at A (1s) and B (1s) exciton resonance of WSe 2 at 4 K ( Figure 4A). 66 Janisch et al calculated χ (2) of WS 2 in the range of 0.5 to 2.5 eV, and the excitonic-enhanced nonlinear susceptibility was well resolved ( Figure 4B).…”
Section: Excitonic Effect-modulated Nlomentioning
confidence: 96%
“…Malard et al observed that χ (2) was enhanced for about four times when SHG energy was in resonance with the C exciton of MoS 2 . Since then, both the experiments and calculations indicated that A and B exciton could also enhance SHG . Typically, Wang et al recorded an enhancement up to three order of magnitude at A (1 s ) and B (1 s ) exciton resonance of WSe 2 at 4 K (Figure A) .…”
Section: Modulation and Enhancement Of Nlomentioning
confidence: 96%
See 1 more Smart Citation
“…Different non-linear optical phenomena like second-, third-harmonic generation and four wave mixing (FWM) [5][6][7] can be quite strong in these materials [8][9][10][11][12][13][14][15]. However, the interpretation of the nonlinear optical response is strongly affected by electronic and phonon resonances [16][17][18][19], therefore the knowledge of the interplay between these resonances is desirable.…”
mentioning
confidence: 99%